2003
DOI: 10.4049/jimmunol.170.12.6280
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of NF-κB, AP-1, and C/EBP in Endotoxin-Tolerant Rats: Mechanisms for In Vivo Regulation of Glomerular RANTES/CCL5 Expression

Abstract: Chemokines play a pivotal role in the regulation of inflammatory cell infiltration in glomerular immune injury. To characterize mechanisms relevant for the regulation of chemokine expression in vivo, the LPS-mediated model of renal inflammation in rats was used in which we have previously demonstrated that the chemokine RANTES/CCL5 is expressed and secreted in glomeruli. Glomerular RANTES/CCL5 expression in this model correlated with an increased glomerular binding activity of the transcription factors AP-1, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 57 publications
4
34
0
Order By: Relevance
“…CCL5 is a chemokine expressed commonly in inflammatory environments. It has a described immunomodulatory role in cancer, is also expressed and secreted in kidney glomeruli (46), and has been associated with renal transplant rejection or, alternatively, with long-term function (47,48). In this study, CCL5 mRNA was found to be upregulated long-term posttransplantation (our experiments were performed 3-4 mo posttransplantation) in tolerant kidney allografts compared with syngeneic kidney grafts (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…CCL5 is a chemokine expressed commonly in inflammatory environments. It has a described immunomodulatory role in cancer, is also expressed and secreted in kidney glomeruli (46), and has been associated with renal transplant rejection or, alternatively, with long-term function (47,48). In this study, CCL5 mRNA was found to be upregulated long-term posttransplantation (our experiments were performed 3-4 mo posttransplantation) in tolerant kidney allografts compared with syngeneic kidney grafts (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…As shown in Fig. 8A, there were two putative NF-B binding sites in the proximal promoter region of rat RANTES gene (31). Stimulation of mesangial cells with TNF-␣ increased p65 binding to B elements in rat RANTES promoter, as demonstrated in Fig.…”
Section: C-terminal P65 Nf-b Mediates Its Interaction With Ppar␥-mentioning
confidence: 73%
“…The anti-p65 NF-B antibody (sc-109; Santa Cruz Biotechnology) was added and incubated at 4°C overnight, followed by incubation with protein A-agarose for 1 h. The precipitates were washed, and chromatin complexes were eluted. After reversal of the cross-linking at 65°C for 4 h, the DNA was purified, and ChIP samples were used as a template for PCR using the primer sets for rat RANTES promoter regions (from Ϫ114 to ϩ36) containing two putative B binding sites (31). The sequences of primers used for ChIP assay were as follows: forward, 5Ј-ctgacagcagccagggtttg-3Ј; and reverse, 5Ј-agatgcatgcgttgtctcag-3Ј, which generated a PCR product of 150 bp.…”
Section: Methodsmentioning
confidence: 99%
“…36,54 The study by An et al 26 has indicated that there is an AP-1 response element within the IL-6 promoter. The RANTES/CCL5 promoter displays binding activity with AP-1, C/EBP and NF-kB, 55 while the IL-8 promoter contains NF-kB, AP-1, OCT-1 and C/EBP-binding sites. [56][57][58] The studies by Hadad et al 59 and Clarke et al 60 have revealed that there is a CREB-binding site within the sICAM-1 and IFN-c promoter.…”
Section: Discussionmentioning
confidence: 99%